2020
DOI: 10.3390/jcm9072311
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Propensity Score Matched Analysis Reveals Superiority of Hypothermic Machine Perfusion over Static Cold Storage in Deceased Donor Kidney Transplantation

Abstract: Hypothermic machine perfusion (HMP) has been introduced as an alternative to static cold storage (SCS) in kidney transplantation, but its true benefit in the clinical routine remains incompletely understood. The aim of this study was to assess the effect of HMP vs. SCS in kidney transplantation. All kidney transplants performed between 08/2015 and 12/2019 (n = 347) were propensity score (PS) matched for cold ischemia time (CIT), extended criteria donor (ECD), gender mismatch, cytomegalovirus (CMV) mismatch, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…( 1,2 ) Unlike CS, preservation at physiological temperature maintains metabolic processes which can prevent the accumulation of toxic metabolites, ( 3 ) allows assessment of graft condition prior to transplantation, and makes possible the delivery of therapeutic medications to the donor liver prior to transplantation. Previous investigations have shown that machine perfusion improves clinical outcomes for marginal organs, ( 4‐6 ) and a large prospective trial has already demonstrated the efficacy of NEVLP clinically. ( 7 )…”
mentioning
confidence: 99%
“…( 1,2 ) Unlike CS, preservation at physiological temperature maintains metabolic processes which can prevent the accumulation of toxic metabolites, ( 3 ) allows assessment of graft condition prior to transplantation, and makes possible the delivery of therapeutic medications to the donor liver prior to transplantation. Previous investigations have shown that machine perfusion improves clinical outcomes for marginal organs, ( 4‐6 ) and a large prospective trial has already demonstrated the efficacy of NEVLP clinically. ( 7 )…”
mentioning
confidence: 99%
“…Almost all kidneys underwent hypothermic machine perfusion in this study (> 90%). Pumping kidneys has been shown to decrease the incidence of DGF in DBD and DCD donor kidneys 38–40 . Additional studies and a Cochrane Review have even shown improved 1‐year and 3‐year graft survival rates for DCD donor kidneys preserved with machine perfusion compared to static cold storage 38,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Pumping kidneys has been shown to decrease the incidence of DGF in DBD and DCD donor kidneys. [38][39][40] Additional studies and a Cochrane Review have even shown improved 1-year and 3-year graft survival rates for DCD donor kidneys preserved with machine perfusion compared to static cold storage. 38,41 New perfusion technologies such as Hypothermic Oxygenated Machine Perfusion (HOPE) and Normothermic Machine Preservation may provide additional benefits, but both of these technologies are in their infancy and require additional resources that may make widespread clinical use challenging.…”
Section: F I G U R E 1 Actuarial Patient Survival Rates Among the Fou...mentioning
confidence: 99%
“…HMP operates with a cold preservation solution and continuously perfuses the organ at a controlled, low flow [ 19 ]. HMP has been associated with significantly lower rates of delayed graft function (DGF) and an increased 1-year graft survival compared to SCS [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Bridging Time To Transplantation—from Static Cold Storage To Machine Perfusionmentioning
confidence: 99%